Self-regulated Learning among University Students (Journal of the College of Basic Education, 2026)
The current research aims to identify the level of self-regulated learning among university students, as well as the significance of statistical differences in self-regulated learning based on the gender variable (male, female) and the academic specialization variable (scientific, humanities). To achieve the research objectives, the researcher developed a Self-Regulated Learning Scale consisting of 42 items, each with five response options: (Completely applies to me, Always applies to me, Sometimes applies to me, Does not apply, Never applies to me).The researcher extracted the psychometric properties of the scale, including item discrimination and various types of validity (logical, face, and construct validity). Reliability was assessed using the test-retest method and Cronbach’s alpha coefficientThe tool was applied to a randomly selected research sample consisting of 300 third-year students from the morning studies at the University of Kirkuk, with 150 students from scientific colleges and 150 from humanities colleges.The statistical methods used in the research included: Chi-square, Pearson correlation coefficient, Cronbach’s alpha coefficient, one-sample t-test, independent samples t-test, and arithmetic mean.The results of the study revealed that students possessed a high level of self-regulated learning. No statistically significant differences were found based on gender (male, female) or academic specialization (scientific, humanities)،In light of the research findings, several recommendations and suggestions were formulated.